Castells, 'Murdochization', economic counterpower and livestreaming. (October 2017) - David, Matthew; Kirton, Andrew; Millward, Peter
In his Information Age trilogy, Manuel Castells documents the transformation of economic power by means of network affordances. In more recent work, he has built an account of the linking of economic power with cultural and political power through 'Murdochization' or 'the networking of networks'. Whilst Castells' account of power has thus developed to acknowledge the integration of economic, cultural and political interests within networks, his account of 'counterpower' remains largely focused on cultural and political resistance in the form of protest. Here we explore a case of economic counterpower, the unauthorized livestreaming of digital sports broadcasts. Analysis of this particular case (of counterpower) is particularly significant, given the centrality of Murdochization in Castells' account of power in the network society. Emerging out of, alongside, and in response to the growth of, Murdochized digital media sports networks, we explore the scope and limits of livestreaming as a form of economic counterpower and counter-Murdochization. In this article, we document Castells' theory of network power, the centrality of Murdochization to that account, and the centrality of monopoly control over digital sports broadcasting to Murdochized media empires. The scope and resilience of alternative streaming media in switching live sports programming from pay to view to free sharing is then examined. The failure to date of all attempts to prohibit free streams shows the ongoing viability of such economic counterpower. However, whilst dominant actors cannot eliminate economic counterpower, where dominant actors choose not to broadcast, no switching of content can take place.